Analysis Of Pedestrian Behaviour Attributes In Rail Transit Terminal Based On Pedestrian Spatial Interaction - Kasehyani, Nur Hanis (2019)
Understanding the dynamics of a crowd is fundamental in planning and managing pedestrians' flow of large public buildings and urban environments. In this study, computational analysis was conducted to investigate pedestrian behaviour attributes in Rail Transit Terminal (RTT) by considering different pedestrian activities while walking based on spatial interaction. The study was piloted at the largest RTT in Kuala Lumpur. The objectives were to empirically determine pedestrian behaviour attributes based on spatial interaction and formulate pedestrian perception domain concerning Malaysian pedestrian in RTT. A total of 359 numbers of pedestrian (NOP) were chosen from 26 recorded videos. The chosen pedestrian was divided into two categories, (1) gender; (2) secondary activities while walking (carrying luggage and using gadget specifically smartphone while walking). Four pedestrians' behaviour attributes were investigated empirically, namely walking velocity, psychological distance, angular velocity and angle of avoidance, with the extension of density relation and formulation of pedestrian perception domain. From the findings, female pedestrians who walk while carrying luggage recorded the lowest average walking velocity, 1.27 m/s followed by males with luggage (1.36 m/s), female and male using gadget while walking (1.37 m/s). Meanwhile, for the pedestrian psychological distance, males using gadget while walking recorded the highest with 3.72 m, and males with luggage recorded the lowest distance with 3.12. When classified according to distance zone proposed by Hall, 1966, 54% of pedestrian average psychological distance falls in the social distance (1.20 – 3.60 m) and 46% fall in public distance (3.60 – 7.60 m). This indicates that chosen pedestrians were individual pedestrian that has no relation with other pedestrians (stranger) around them. For the pedestrian angular velocity, where males with luggage recorded the highest velocity (2.18 rad./s) and females who walk without any activity recorded the lowest velocity (0.96 rad./s). The final attribute, the pedestrian angle of avoidance, male with luggage recorded the highest (49.94o) and female without any secondary activity while walking recorded the lowest (21.98º). Last, the formulation of pedestrian perception domain from obtained pedestrian behaviour attributes was conducted to represent pedestrian interaction in RTT. It is believed that different pedestrian activities contributed to different behaviour attributes in RTT. Through the understanding of pedestrian, behaviour attributes in RTT at Malaysia allow the infrastructure planner and policymakers to predict future walking behaviour and plan the strategic alternative for a continuation of smooth pedestrian movement.